Upaya Desa Gamplong Sebagai Desa Wisata Industri Alat Tenun Bukan Mesin Dalam Meningkatkan Pendapatan Masyarakat - Emmita Devi Hari Putri - AKPAR BSI Yogyakarta (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2015)
Abstract Small and Medium Enterprises (SMEs) which was developed in a village can have a positive impact for the local community, especially in terms of the economy. But in reality still lack of innovation in the communities can inhibit the development of SMEs. In this study the authors took place in the village Gamplong research, Sumber Rahayu, Moyudan, Sleman, Yogyakarta. Methods of research used qualitative research methods which in this study the authors describe only on a natural phenomenon in a systematic, factual, and accurate. Explain or describe the study variables without seeking the association between the variables with other variables. This means that this study is limited to the disclosure of business problems and circumstances as in fact only a disclosure of facts. Hamlet Gamplong, Source Rahayu, Moyudan is one part of the development of natural and cultural tourism village crafts. Craft developed in the village is a tourist village which Weaving craft manufacturing process still uses Not Weaving Machine Tools (handloom). Given the hamlet Gamplong as a tourist attraction that can bring in more tourists, the community Gamplong develop a variety of facilities, infrastructure and facilities needed by tourists. With the development of tourist villages can help communities Gamplong industry in terms of improving people's income. Keyword: Tourist Village Industries , Not Weaving Machine Tools , Community Income